Approximation by a generalization of Szász-Mirakjan type operators - ARIF SIDDIQUI, Mohammed; GUPTA, Nandita (Studia Universitatis Babeș-Bolyai Mathematica, 2020)
In the present paper we propose a new generalization of Szász - Mirakjan-type operators. We discuss their weighted convergence and rate of convergence via weighted modulus of continuity. We also give an asymptotic estimate through Voronovskaja type result for these operators. Mathematics Subject Classification (2010): 41A36.